Penerapan Prinsip 5S dalam Meningkatkan Efisiensi dan Mengurangi Waste Montion Pada PT. XYZ dengan Pendekatan Lean Manufacturing - Nando, Fiky Two; Ramadhan, Muhammad Ilham; Wicaksono, Rendy Bagus; Cahyani, Andini Putri; Anindita, Imara Hany; Prabandari, Anggraeni Sih (Indonesian Journal of Engineering and Technological Innovation, 2025)
PT. XYZ is a company engaged in the furniture industry, with one of its main products being wooden doors, which serve as the object of analysis in this final project. Based on historical data from June 2025 to October 2025, there is a gap between the actual production output and the company’s target. This shortfall is indicated to be caused by waste occurring throughout the production process. Through the lean manufacturing approach, the types and causes of waste were identified using Value Stream Mapping (VSM) and Process Activity Mapping (PAM). The mapping results show a total production lead time of 4,320 seconds and reveal the presence of Non-Value-Added (NVA) activities that affect production performance. The waste with the highest percentage is motion waste, accounting for 66%, which becomes the focus of this study. The root causes of motion waste were analyzed using the 5 Whys method to determine the source of activities that do not add value. Based on the results of this analysis, improvement plans were developed through the implementation of 5S activities (seiri, seiton, seiso, seiketsu, and shitsuke) to minimize motion waste. The implementation of the proposed improvements shows that the total lead time has the potential to decrease and can be further enhanced through continuous kaizen efforts.